The Effects of Problem-Based, Project-Based, and Multicultural Learning on Prosocial Behavior in Elementary School Students - Danang Prastyo; Budi Eko Soetjipto; Syamsul Hadi; Ari Sapto Sapto (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the influence of Problem-Based Learning, Project Based Learning and Multicookural Based Learning on prosocial behaviour in elementary school students. This study is a type of quasi-experimental research with a model using theÂ Nonequavalen Control Group Postest Design. The research population consisted of 284 public elementary schools (SD) in Surabaya. In comparison, the research sample consisted of grade V students in three schools, namely SDN Margerejo I, SDN Sumur Welut III Surabaya, andÂ SDN Menanggal 601 Surabaya. The data collection technique uses a questionnaire with 30 questions. The research instrument used the Measure of Prosocial Tendencies by adapting Carlo. Data analysis with statistical analysis of ANOVA test. The results of this study concluded the effect of project-based learning on prosocial behaviour in elementary school students with an ANOVA test score sig. < 0.05. These findings show that the project-based learning model can foster prosocial behavior in elementary school students.